Reported Technical Aspects of Type II SLAP Lesion Repairs in Athletes - Jack W. Weick, M.D; Will B. Workman, M.D; Christopher J. Bush, M.D; Katherine A. McCollum, B.S; Hiroyuki Sugaya, M.D; Michael T. Freehill, M.D (Elsevier, 2021)
Purpose: To systematically review the available literature to further describe and report the available data on SLAP repair techniques and the association with outcomes. Methods: A systematic review of literature was performed on manuscripts describing type II SLAP repairs in athletes. Selection criteria included studies reporting exclusively type II SLAP tears without concomitant pathology, minimum 2-year postoperative follow-up, use of anchor fixation, and return to previous level of play data available. We extracted patient outcome as well as surgical construct details from each article. Average outcomes and return to play rates were calculated and substratified further by athlete type. Return to play rates were compared by repair constructs with the Student t test. Results: Initial search resulted in 107 articles. After exclusion criteria were applied, 17 articles were included in the final analysis. Overall, 84% of patients had good-to-excellent results. Of all athletes, 66% returned to previous level of play. There was significant variation in reported technique in terms of anchor number, location, material, suture type, and knotless versus knotted constructs. No significant difference was reported in outcomes in comparison of suture type (P-value .96) or knotted versus knotless constructs (P-value .91). Given the significant variability in reporting, no statistical analysis was felt able to be performed on anchor location and number. Conclusions: Repair of type II SLAP tears in athletes is a difficult problem to treat with overall low return to play despite a high rate of "good" outcomes when assessed by outcome measures. Significant variability exists in surgical technique, as well as reporting of surgical technique, potentially limiting the ability to define the best or most effective technique for SLAP repair. Level of Evidence: IV, systematic review of level III and level IV studies.